Epitope analysis of Ara h 2 and Ara h 6: characteristic patterns of IgE‐binding fingerprints among individuals with similar clinical histories. Issue 2 (February 2015) - Otsu, K.; Guo, R.; Dreskin, S. C.
Summary Background Ara h 2 and Ara h 6 are moderately homologous and highly potent peanut allergens. Objective To identify IgE‐binding linear epitopes of Ara h 6, compare them to those of Ara h 2, and to stratify binding based on clinical histories. Methods Thirty highly peanut‐allergic subjects were stratified by clinical history. Sera were diluted to contain the same amount of anti‐peanut IgE. IgE binding to overlapping 20‐mer peptides of Ara h 2 and Ara h 6 was assessed using microarrays. Results Each subject had a unique IgE‐binding fingerprint to peptides; these data were coalesced into epitope binding. IgE from subjects with a history of more severe reactions (n = 19) had a smaller frequency of binding events (BEs) for both Ara h 2 (52 BEs of 152 (19X8epitopes) possible BEs and Ara h 6 (13 BEs of 133 (19X7 epitopes) possible BEs) compared to IgE from those with milder histories (n = 11) (Ara h 2: 47 BEs of 88 (11X8 epitopes) possible BEs, P < 0.01; Ara h 6: 25 BEs of 77 (11X7 epitopes) possible BEs, P < 0.001). Using an unsupervised hierarchal cluster analysis, subjects with similar histories tended to cluster. We have tentatively identified a high‐risk pattern of binding to peptides of Ara h 2 and Ara h 6, predominantly in subjects with a history of more severe reactions (OR = 12.6; 95% CI: 2.0–79.5; P < 0.01). Conclusions and Clinical Relevance IgE from patients with more severe clinical histories recognize fewer linear epitopes of Ara h 2 and Ara h 6 than do subjects with milder reactions and bind these epitopes in characteristic patterns. Close examination of IgE binding to epitopes of Ara h 2 and Ara h 6 may have prognostic value.